2012
DOI: 10.1002/prot.24046
|View full text |Cite
|
Sign up to set email alerts
|

The nature of tryptophan radicals involved in the long‐range electron transfer of lignin peroxidase and lignin peroxidase‐like systems: Insights from quantum mechanical/molecular mechanics simulations

Abstract: A catalytically active tryptophan radical has been demonstrated to be involved in the long-range electron transfer to the heme cofactor of lignin peroxidase (LiP) from Phanerochaete chrysosporium although no direct detection by EPR spectroscopy of the tryptophan radical intermediate has been reported to date. An engineering-based approach has been used to manipulate the microenvironment of the redox-active tryptophan site in LiP and Coprinus cinereus Peroxidase (CiP), allowing the direct evidence of the trypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…It has been shown that methionine residues play a role in the electrostatic stabilization of Trp protein radicals 47,25,62,[66][67][68] .…”
Section: Lret Pathway/s In Aaudypmentioning
confidence: 99%
“…It has been shown that methionine residues play a role in the electrostatic stabilization of Trp protein radicals 47,25,62,[66][67][68] .…”
Section: Lret Pathway/s In Aaudypmentioning
confidence: 99%
“…QM calculations at a DFT level (mainly B3LYP functional) have been used together with experimental data from multifrequency electronic paramagnetic resonance (EPR) and pulse electron nuclear double resonance (ENDOR) experiments to study the nature of the tryptophan radical (Trp164) of VP from Pleurotus eryngii [59]. Here, Pogni et al through the calculations of g-tensors, hyperfine (hf) couplings and spin densities identified that the radical form of Trp164 most likely corresponds to a neutral radical and not a cationic radical as it was thought to be for Trp171 from LiP [60]. However, it is very likely that the tryptophan cationic radical is indeed an intermediate which then becomes deprotonated at the indole nitrogen by Glu243, which is forming a hydrogen bond at this position, to form the more stable neutral radical [59].…”
Section: Versatile Peroxidasementioning
confidence: 99%
“…Smith et al also studied different LiP variants (E168Q, E250Q and E250Q/E168Q) to compare the results obtained with the new-engineered CiP. Thus, in the theoretical work of Bernini et al [60] three systems were studied namely pristine LiP, the LiP variant E250Q/E168Q and the CiP variant D178W/R257E/R271D to allow direct comparison with the experimental data available for the last two systems. The values for g-tensors and hf coupling constants were calculated for the corresponding neutral and cationic radicals.…”
Section: Lignin Peroxidase (Lip)mentioning
confidence: 99%
See 2 more Smart Citations